2021
DOI: 10.1111/febs.16035
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma: from discovery to clinical management

Abstract: Abbreviations: Retinoblastoma protein/gene (RB/RB1); External Beam Radiotherapy (EBRT); intravenous chemotherapy (IVC); vincristine, etoposide and carboplatin (VEC); intra-arterial chemotherapy (IAC); intraocular classification of retinoblastoma (ICRB); Proton beam radiation therapy (PBRT); the transforming growth factor b1 (TGF-b1); senescence-associated heterochromatic foci (SAHF); lactate dehydrogenase (LDH); no-homologous end joining (NHEJ); homologous recombination (HR); methyltransferase 1 (DNMT1); DNA-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 92 publications
(98 reference statements)
0
11
0
Order By: Relevance
“…Human RB protein (pRB) has a mass of 106 kDa (106,159 Da) and consists of 928 amino acids. It has been demonstrated that this protein functions in a wide network of molecular interactions [ 3 , 18 ]. The function and the structure of this protein has been extensively studied for decades; however, its many molecular functions still need investigation.…”
Section: Prb Protein Structure and Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human RB protein (pRB) has a mass of 106 kDa (106,159 Da) and consists of 928 amino acids. It has been demonstrated that this protein functions in a wide network of molecular interactions [ 3 , 18 ]. The function and the structure of this protein has been extensively studied for decades; however, its many molecular functions still need investigation.…”
Section: Prb Protein Structure and Functionmentioning
confidence: 99%
“…pRB protein versatile functions are illustrated by many different protein interactions it performs. Besides E2F family members, pRB interacts with chromatin modifiers such as DNMT1, HDAC, SIRT1, the replication factor C, the DNA polymerase α, MDMX and MDM2 [ 3 ]. For example, it has been shown that MDM2 is an important regulator of the RB activity with dual roles, when in G1 phase it can bind to the RB mRNA and enhance the RB translation, while during G2 MDM2 can degrade pRB.…”
Section: Prb Protein Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In children, retinoblastoma (Rb) is a relatively common human genetic malignant ocular tumour (1)(2)(3)(4). It has the characteristics of high incidence, and low survival rate usually occurs in children under 3 years old and can affect one or both two eyes and seriously affect the health of children (5)(6)(7). Rb can be divided into two genetic modes: germline inheritance and non-germline inheritance (8).…”
Section: Introductionmentioning
confidence: 99%
“…Research into novel biomarkers is an effective way to improve the probability of satisfactory outcomes, including the prognosis and quality of life in patients with retinoblastoma. Although new molecular biomarkers for retinoblastoma have been revealed in recent years [7][8][9][10][11], they are still in the experimental stage and have not been approved for clinical use [12]. Currently, there is no gold standard biomarker for the diagnosis and treatment of retinoblastoma.…”
Section: Introductionmentioning
confidence: 99%